STUDENTS’ CHALLENGES IN LITERATURE COURSES ONLINE LEARNING: STUDENTS’ PERCEPTIONS CASE STUDY - I.G.A. Lokita Purnamika Utami; Putu Eka Dambayana Suputra; Ida Ayu Gede Juliana Dewi (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2021)
This research aimed at investigating the challenges encountered by the students when utilizing Undiksha Moodle E-learning in online learning of literature courses. The research used embedded mixed method case study with qualitative dominant in collecting the data. The research subjects were students of English Language Education (ELE) who learned Literature courses by using Undiksha Moodle E-Learning platform. Questionnaire and semi-structured interview guide were used by the researcher as the instruments. The result of this study shows that there were 5 challenges encountered by the students in operating Undiksha Moodle E-learning platform which could be categorized into two namely internal and external challenges. The internal challenges were the absence of some features such as video conference feature, assignment pop-up reminder feature, the occurrence of server crash and the external challenges was the inequality of internet connection quality